Biofertilizer and biostimulant properties of the microalga Acutodesmus dimorphus - Garcia-Gonzalez, Jesus; Sommerfeld, Milton (Journal of applied phycology, 2016)
Microalgae represent a potential sustainable alternative for the enhancement and protection of agricultural crops. Cellular extracts and dry biomass of the green alga Acutodesmus dimorphus were applied as a seed primer, foliar spray, and biofertilizer, to evaluate seed germination, plant growth, and fruit production in Roma tomato plants. A. dimorphus culture, culture growth medium, and different concentrations (0, 1, 5, 10, 25, 50, 75, and 100 %) of aqueous cell extracts in distilled water were used as seed primers to determine effects on germination. Seeds treated with A. dimorphus culture and with extract concentrations higher than 50 % (0.75 g mL⁻¹) triggered faster seed germination—2 days earlier than the control group. The aqueous extracts were also applied as foliar fertilizers at various concentrations (0, 10, 25, 50, 75, and 100 %) on tomato plants. Extract foliar application at 50 % (3.75 g mL⁻¹) concentration resulted in increased plant height and greater numbers of flowers and branches per plant. Two dry biomass treatments (50 and 100 g) were applied 22 days prior to seedling transplant and at the time of transplant to assess whether the timing of the biofertilizer application influenced the effectiveness of the biofertilizer. Biofertilizer treatments applied 22 days prior to seedling transplant enhanced plant growth, including greater numbers of branches and flowers, compared to the control group and the biofertilizer treatments applied at the time of transplant. The A. dimorphus culture, cellular extract, and dry biomass applied as a biostimulant, foliar spray, and biofertilizer, respectively, were able to trigger faster germination and enhance plant growth and floral production in Roma tomato plants.